Neck Chamber Technique Revisited: Low-Noise Device Delivering Negative and Positive Pressure and Enabling Concomitant Carotid Artery Imaging With Ultrasonography - Seredyński, Rafał; Okupnik, Tymoteusz; Musz, Przemysław; Tubek, Stanisław; Ponikowska, Beata; Paleczny, Bartłomiej (Frontiers in Physiology, 2021)
Background & Objectives: Recently, novel noiseless device for the assessment of baroreceptor function with the neck suction (NS) has been presented. In this study, we present another in-house approach to the variable-pressure neck chamber method. Our device offers further critical improvements. First, it enables delivery of negative (NS) as well as positive pressure (neck pressurizing, NP) in a noiseless manner. Second, we used small, 3D-printed cups positioned over the carotid sinuses instead of cumbersome neck collar to improve subject comfort and to test feasibility of tracking the pressure-induced changes in carotid artery with ultrasonography. Methods: Five healthy, nonsmoking, normal-weight subjects aged 29±3 years (mean±SD) volunteered for the study. Heart rate (HR, bpm) and mean arterial pressure (MAP, mmHg) responses to short, 7-second long episodes of NS and NP were recorded. Each trial consisted of 12 episodes of variable-pressure: six episodes of NS (suction ranging between -10 to -80 mmHg) and six episodes of NP (pressure ranging between +10 and +80 mmHg). Carotid artery sonography was performed during the NS and NP in four subjects, on another occasion. Results: The variable-pressure episodes resulted consistently in the expected pattern of hemodynamic alterations: HR and MAP increases or decreases following the NP and NS, respectively, as evidenced by the coefficient of determination (R2) of ≥0.78 for the carotid-HR response curve (for all five participants) and the carotid-MAP response curve (for four out of five participants; the curve cannot be calculated for one subject). We found a linear, dose-dependent relation between the applied pressure and the systolic-diastolic difference in carotid artery diameter. Conclusions: The novel device enables noiseless stimulation and unloading of the carotid baroreceptors with the negative and positive pressure, respectively, applied on the subject’s neck via small, asymmetric and one-side flattened, 3D-printed cups. The unique design of the cups enables concomitant visualizing of the carotid artery during the NS or NP administration, and thereby direct monitoring of the intensity of mechanical stimulus targeting the carotid baroreceptors.